Elliptical mirrors : applications in microscopy - Liu, Jian (Professor of electrical engineering and automation) (IOP (Series). Release 5., 2018)
Composed by a specialist in the field, Professor Jian Liu and with the members of his team contributing to the work, Elliptical Mirrors discusses the importance of the elliptical mirror, the third solution in far field optical imaging after parabolic reflectors and lenses for which apodization factors were established in 1921 and 1959 respectively. Elliptical Mirrors are a new and novel technique within the world of optics and can be applied to industrial imaging, bio-imaging, x-ray photography and much more. Elliptical mirrors are inevitably going to retain a significant role in trend of microscopic development. This detailed and highly insightful book will be an important insight into a growing subject area that will benefit PhD students, optical physicists, metrologists and researchers who have an interest in the ever-growing science of optics. The book discusses the original concept of elliptical mirrors and gives a fundamental and comprehensive theory behind them and their functions.